A rede construída por nós : extensão rural, novas ruralidades e cotidiano em Barra do Riachão, Pernambuco - LAURENTINO, Auta Luciana (2011)
This paper addresses a study on new ruralities in which hand made production is presented as one of the existing occupations in rural areas that enable the dynamization of the families in their communities. Barra do Riachão, a district of São Joaquim do Monte/ PE, is the locus of this research. The theoretical framework emphasizes the following categories: rural extention, new ruralities, local development, and also everyday life and imaginary.We bring the concepts of Del Grossi and Graziano da Silva (2002), Markus Brose (2004) and José Marcos Froehlich (2002), which deal with on new ruralities and their consequences; Callou (2007), Jesus (2003/2007) and Tauk Santos (2000 / 2002 / 2008) under the framework of local development are employed. In the caregory of everyday life, the theories of Michel de Certeau (2008/ 2009) and Almeida (1999/ 2000). At first, the applied methodology performs an analysis of the theoretical concepts that give support to the empirical research. In this phase, the resource of oral history is applied using the concepts of Paul Thompson (1992) and Ecléa Bosi (1994) and their studies of memory. The findings of the research were analyzed with the assistance of the theoretical methodology of Discourse Analysis (DA), for the deconstruction of speech production, Orlandi (2005). This is a qualitative study in which data was collected through semi-structured interviews, starting with the concepts of Minayo (1996) and Chizzotti (2006). The interviews were administered with direct contact to residents and artisans of the community, therefore allowing the comprehension of spontaneously statements, for a subsequent analysis, with Szymanski (2004) and Boaventura de Sousa Santos (2008). As well, in order to understand the acceptance of group production of Barra do Riachão, we conducted interviews with some visitors on a major national events focused on the marketing of handicrafts. As a result, the research reveals the need for more investment in public policies related to the reality of rural areas.